(3GdJaGhV hGOQGI GdGReGJs - (3YKeGf(B, (3aGQhb GdSjOs ((3GdbGgQIs (3OGQ GdGejf WHYs, 2004)
(3SjchdhLjI GdJaGhV ; GSJQGJLjI JfejI GdegGQGJ GdSdhcjI aj GdYedjI GdJaGhVjI ; GdLhGfH GdOGaYjI hGdhLOGfjI aj YedjI GdJaGhV ;OhQ GdbGjOI hGdeRGL aj GdYedjI GdJaGhVjI ; SchdhLjI GOGQI GdGReGJ hGdGJUGd aj Gdehba GdJaGhVjs
Keywords: (3GOGQI GReGJ(B- (3JaGhVs